"Impressionantes esculturas de lama": a patrimonialização do Manguebeat (1997 - 2012) - Oliveira, Esdras Carlos de Lima (2020)
The persons who walk through the city of Recife, especially in the central neighborhoods, can see the presence of two figures in many places: Chico Science, a singer and composer, and the other, the crabs. These two symbols are connected to the Manguebeat scene that developed in the city in the 1990s, with a mix of regional and global rhythms, this was its main brand. In addition to these spatial landmarks, part of the cultural production promoted by municipal administrations between 2000 and 2012 had the idea of Manguebeat as a reference. These administrations used the elements from the Manguebeat as the basis for the construction of public policies and symbolic places. After this process occured the implementation of patrimonialization actions about Manguebeat, such as the aforementioned sculptures and the creation of a memorial to celebrate the figure of Chico Science. The cultural journalism of the city through its culture notebooks collaborated to build from the same references a similar narrative after the death of Chico in 1997 and use it on commemorative dates related to him, such as his birthday of birth and the day of his death. On this path, public power and private power, together, elaborated with specific interests discourses about Manguebeat that integrated into the symbolic ideas about Recife and its culture, in the midst of a process that this thesis is willing to analyze.